THE ETERNAL WINTER OF AFFECT: VERNE’S AVANT-GARDISM AND THE FAILURE TO PROTECT HUMAN DIGNITY - Edstron Secundino Santos, Júlio (Revista Gênero e Interdisciplinaridade, 2026)
This article investigates the dystopian technocracy in Jules Verne’s literary work Paris in the Twentieth Century, analyzing it as a terrifying prelude to contemporary psychological pathologies. The primary relevance of this research lies in the urgency of understanding the profound current civilizational malaise, clearly demonstrating how technical hegemony and the relentless acceleration of vital time have fragmented human subjectivity and transformed the pursuit of happiness into an exhausting performance-driven journey. A qualitative, exploratory, and bibliographical methodology was adopted, structured under an interdisciplinary approach. The research trajectory consisted of a meticulous examination of the Vernian narrative, placing it in tension with theories from contemporary sociology, philosophy, and psychoanalysis, correlating the 1863 fiction with concepts such as the burnout society and liquid modernity. It concludes that the current emotional collapse materializes the nineteenth-century nightmare, where the submission of Law to a purely economic logic crushes human fragility. The fragmentation of fundamental guarantees urgently demands the revaluation of rest, communal solidarity, and contemplation in the face of technological voracity, an essential step to rescue mental health and the human dignity forgotten amidst utility.